Application of bedside ultrasound-guided nasointestinal tube placement in critically ill patients during the recovery period (床旁超声定位引导鼻肠管置管在重症康复患者中的应用) - ZHONG Lirong (钟丽容); HUANG Chunxia (黄春霞); CHEN Fengzhen (陈凤珍); WANG Yingmin (王颖敏) (中西医结合护理)
Objective To investigate the safety and feasibility of bedside ultrasound-guided nasointestinal tube placement in critically ill patients during the recovery period. Methods A retrospective analysis of 52 critically ill patients who met the criteria of nasointestinal tube placement during the recovery period was conducted. Guided by the bedside ultrasound, the nasointestinal tube was passed via the nose into the oesophagus, on into the stomach, through the pylorus and into the duodenum or jejunum, the position of the catheter was confirmed by X-ray. Results The success rate of intubation was 96. 15%(50/52). All patients' vital signs were stable during placement, and no complications such as nasal bleeding, accidental airway entry, gastrointestinal bleeding or perforation occurred. Conclusion The bedside ultrasound-guided nasointestinal tube placement has a good outcome in critically ill patients during the recovery period, can improve the success rate of intubation, and has a certain safety. (目的 观察床旁超声定位引导鼻肠管置管在重症康复患者床旁实施的安全性及可行性。方法 回顾性分析2020年2月—2024年8月医院康复医学科住院符合鼻肠管置管指征的患者52例, 采用床旁超声引导辅助鼻肠管置管, 即通过超声探查鼻肠管在食道内、胃内及幽门后, 最后X线确认鼻肠管头端位置。结果 共52例留置鼻肠管患者, 置管成功50例, 置管成功率为96. 15%。所有患者在置入过程中生命体征平稳, 均未发生鼻腔出血、误入气道、消化道出血或穿孔等相关并发症。结论 超声实时定位引导鼻肠管置管在重症康复患者床旁实施安全可行, 置管成功率高。)